Pediatric nephrology Volume 1 - Avner, Ellis D.; Harmon, Willam E.; Niaudet, Patrick; Emma, Norishige Yoshikawa Francesco; Goldstein, Stuart L. (New York Springer, 2009)
This book serves as a superb reference and is an invaluable asset during clinical encounters with children having all forms of kidney disease.
Keywords: Y Đa khoa